The IRAP guidebook Integrated Rural Accessibility Planning for Local Governments. (DILG and ILO, 2002)
This Guidebook aims to provide planners and decision-makers particularly of local government units (LGUs) with an easy reference to the application of the integrated rural accessibility planning procedure. It is hoped that through this guidebook, planners and decision-makers can easily and inexpensively establish, update their accessibility databases and use the accessibility information in ensuring a more effective delivery of basic goods and services.